Trend in Infant and Young Child Feeding practices during 2005 – 2015 in India - Kapil, Umesh; Gupta, Aakriti (Indian Journal of Community Health, 2016)
Background: Optimal infant and young child feeding (IYCF) practices during first 2 years of life is the key to ensuring optimal growth and development of the infant. Improving IYCF practices have an important role in reducing morbidity and mortality amongst under 5 children in India. Material & Methods: The secondary data from National Family Health Survey (NFHS)-3 and NFHS- 4 was analyzed. Objective: To assess the trend in IYCF practices during 2005 – 2015 for 13 selected states of India. Results: It was found that over a decade, there has been an improvement in early initiation of breast feeding and exclusive breastfeeding for 6 months amongst infant in 11 out of 13 states. However, a reduction in the timely initiation of complementary feeding amongst children in the age group of 6-8 months has been observed in 9 out of 13 states. Conclusion: There is a need to strengthen the efforts to further improve the IYCF practices in India for reducing high rates of undernutrition in the country.